Amine functionalized radiation induced grafted polyolefin nanofibers for CO2 adsorption - Abbasi, A. (2019)
A new type of nanofibrous amine-containing adsorbent was prepared for CO2 adsorption by electrospinning of syndiotactic polypropylene (s-PP) followed by radiation induced grafting of glycidyl methacrylate and subsequent amination with ethanolamine. The obtained adsorbents were tested for CO2 adsorption with a mixture of CO2/N2 having 5â15 CO2 using a fixed bed adsorption column at atmospheric pressure. A maximum adsorption capacity of 2.87 mmol/g was achieved for the sample with degree of grafting of 300 and degree of amination of 94 at feed concentration of 15 at 30 Â°C. This was accompanied by good mechanical characteristics and a very high amine efficiency that reached 75 at room temperature, suggesting that the obtained fibrous adsorbent has high potential for CO2 adsorption. Â© 2018 Elsevier Ltd